The L–VP35 and L–L interaction domains reside in the amino terminus of the Ebola virus L protein and are potential targets for antivirals - Trunschke, Martina (2013)
The Ebola virus (EBOV) RNA-dependent RNA polymerase (RdRp) complex consists of the catalytic subunit of the polymerase, L, and its cofactor VP35. Using immunofluorescence analysis and coimmunoprecipitation assays, we mapped the VP35 binding site on L. A core binding domain spanning amino acids 280– 370 of L was sufficient to mediate weak interaction with VP35, while the entire N-terminus up to amino acid 380 was required for strong VP35–L binding. Interestingly, the VP35 binding site overlaps with an N-terminal L homo-oligomerization domain in a non-competitive manner. N-terminal L deletion mutants containing the VP35 binding site were able to efficiently block EBOV replication and transcription in a minigenome system suggesting the VP35 binding site on L as a potential target for the development of antivirals.